Recycling of single-stranded DNA-binding protein by the bacterial replisome. Issue 8 (15th February 2019) - Spenkelink, Lisanne M; Lewis, Jacob S; Jergic, Slobodan; Xu, Zhi-Qiang; Robinson, Andrew; Dixon, Nicholas E; van Oijen, Antoine M
Abstract: Single-stranded DNA-binding proteins (SSBs) support DNA replication by protecting single-stranded DNA from nucleolytic attack, preventing intra-strand pairing events and playing many other regulatory roles within the replisome. Recent developments in single-molecule approaches have led to a revised picture of the replisome that is much more complex in how it retains or recycles protein components. Here, we visualize how an in vitro reconstituted Escherichia coli replisome recruits SSB by relying on two different molecular mechanisms. Not only does it recruit new SSB molecules from solution to coat newly formed single-stranded DNA on the lagging strand, but it also internally recycles SSB from one Okazaki fragment to the next. We show that this internal transfer mechanism is balanced against recruitment from solution in a manner that is concentration dependent. By visualizing SSB dynamics in live cells, we show that both internal transfer and external exchange mechanisms are physiologically relevant.